Determinants of maximal oxygen uptake in moderate acute hypoxia in endurance athltes - Mollard, P.; Woorons, X.; Letournel, M.; Lamberto, C.; Favret, F.; Pichon, A.; Beaudry, M.; Richalet, J. P. (12th Annual Congress of the European College of Sport Science, Jyväskylä, Finland - July 11-14th 2007, 2007)
The factors determining maximal oxygen consumption were explored in eight endurance trained subjects (TS) and eight untrained subjects (US) exposed to moderate acute normobaric hypoxia. Subjects performed maximal incremental tests at sea level and simulated altitudes (1000, 2500, 4500 meters). Heart rate (HR), stroke volume (SV), cardiac output (Q), arterialized oxygen saturation (Sa`O2), oxygen uptake (VO2max), ventilation (VE, expressed in normobaric conditions) were measured. At maximal exercise, ventilatory equivalent (VE/VO2max), O2 transport (QaO2max) and O2 extraction (O2ERmax) were calculated. In TS, Qmax remained unchanged despite a significant reduction in HRmax at 4500m. SVmax remained unchanged. VEmax decreased in TS at 4500m, VE/VO2max was lower in TS and greater at 4500m vs sea level in both groups. Sa`O2max decreased at and above 1000m in TS and 2500m in US, O2ERmax increased at 4500m in both groups. QaO2max decreased with altitude and was greater in TS than US up to 2500m but not at 4500m. VO2max decreased with altitude but the decrement was larger in TS at 4500m. In both groups VO2max decrement in moderate hypoxia was correlated with QaO2max decrement. Several differences between the two groups are probably responsible for the greater VO2max decrement in TS at 4500m: 1) the relative hypoventilation in TS as shown by the decrement in VEmax at 4500m 2) the greater QaO2max decrement in TS due to a lower Sa`O2max and unchanged Qmax 3) the smaller increase in O2ERmax in TS, insufficient to compensate the decrease in QaO2max.